Study of Serum IgE levels in Recurrent Respiratory illness in children 6 months to 5 years of age - Dr. Rashmi Vishwakarma; Dr. Anita Sharan; Dr. Priti Reddy; Dr. K. Satyanarayana (Pediatric Review: International Journal of Pediatric Research, 2020)
Objective: The present study was undertaken to study the serum IgE levels in recurrent respiratory tract illnesses in children greater than 6 months to less than 5 years of age and to find the correlation between them.Methods: This was a prospective observational cross-sectional study. The study was undertaken to determine the correlation of serum IgE levels with recurrent respiratory tract illness. A total of 99 children were included in this study. 2ml of blood was drawn by peripheral venous phlebotomy in airtight screw-capped plastic vials for measuring serum IgE levels. The Serum IgE level is assessed by chemiluminescence.Results: Out of 99 children, 48 children had elevated serum IgE levels and 51 had normal serum IgE levels. Serum IgE levels were significantly higher (66.07%) in males as compared to females (25.58%) with a p-value of 0.0003 (<0.05). The elevation of serum IgE levels was 48.48% in all children (48 out of 99 children). It’s noticed that the number of children suffering from RRTI and the number of children with elevated serum IgE levels increased with increasing age. There is a significant increase in serum IgE levels from 10.00% in infancy to 64.10% in the 49-60th month.Conclusion: This study showed an increasing number of children with recurrent respiratory tract illness and serum IgE levels with increasing age. Males, preterm and bottle-fed babies are more prone. There was a significant role in a family history of recurrent respiratory tract illness in children with elevated serum IgE levels.